Community perspectives on ideal bacterial STI testing services for gay, bisexual, and other men who have sex with men in Toronto, Canada: a qualitative study - Jayoti Rana; Ann N. Burchell; Susan Wang; Carmen H. Logie; Ryan Lisk; Dionne Gesink (BMC, 2022)
Abstract Background Innovation is needed to produce sustained improvements in bacterial sexually transmitted infections (STI) testing given suboptimal access and uptake among sexually active gay, bisexual or other men who have sex with men (GBM). Yet, the STI testing processes and technologies that best address local testing barriers among GBM in Toronto is unknown. We aimed to explore men's perspectives regarding STI testing services for GBM to identify and prioritize new STI testing interventions in Toronto, Ontario, Canada. Methods We conducted four focus groups with twenty-seven GBM in 2017: two with cisgender men living with HIV, one with cisgender HIV-negative men, and one with transgender men. Twenty-seven men participated in the focus groups with 40% 18-30 years of age, 48% self-identifying as white, and the remainder self-identifying as Middle Eastern, Latino/Hispanic, Asian/Pacific Islander, South Asian, First Nations, African/Caribbean/Black, or mixed race. 59% of participants self-identified as living with HIV. Participants were asked about their STI testing experiences in Toronto, barriers and facilitators to testing, and ideal STI testing process. Focus groups were audio recorded, transcribed verbatim, and analyzed using thematic analysis. Results Core concepts included how clinical context, bacterial STI testing delivery, and interactions with healthcare providers can create barriers and recommendations for ways to improve. Regarding clinical context, participants desired more clinics with accessible locations/hours; streamlined testing that minimized use of waiting rooms and wait times; and improved clinic ambience. Bacterial STI testing delivery recommendations included standardization to ensure consistency in sexual history intake, tests offered, follow-up and public health reporting between clinics. Men also recommended reducing the multistep process testing by offering components such as lab requisitions and results online. Participants also recommended interactions with healthcare providers be professional and non-judgmental, offer compassionate and competent care with destigmatizing and lesbian, gay, bisexual and trans (LGBT) affirming communication. Conclusion Concrete and practical solutions for improving existing sexual health services and facilitating optimal STI testing include streamlining testing options and providing patient-centred, LGBT-affirming care to enable optimal STI testing.